On the fiftieth anniversary Postinfectious irritable bowel syndrome: mechanisms related to pathogens. Issue 2 (February 2014) - Grover, M.; Camilleri, M.; Smith, K.; Linden, D. R.; Farrugia, G.
Abstract Background Gastrointestinal (GI) infections resulting from bacterial, viral, and parasitic pathogens predispose to postinfectious irritable bowel syndrome (PI‐IBS) and other functional GI disorders. Existing literature supports the role of enterochromaffin cell hyperplasia, serotonin synthesis and reuptake, impaired barrier function, altered immune activation, and potentially mast cell activation in the pathophysiology of PI‐IBS. Purpose The objective of this review was to summarize from the literature the characteristics of the pathogens commonly implicated in PI‐IBS, their acute enteritis phases, and the changes seen in the postinfectious phase that may contribute toward development of IBS. A limitation of our current understanding is that the postinfectious GI sequelae reported in prior studies followed epidemic diarrheal outbreaks often involving more than one pathogen, or the studies focused on highly selected, tertiary referral patients. Understanding the mechanisms, natural history, and optimized management of individuals suffering PI‐IBS following the more typical sporadic infection requires larger studies of PI‐IBS following GI infections encountered in community settings. These studies should include genetic, physiological, and molecular studies to provide more generalizable information that can ultimately be used to diagnose, manage, and potentially prevent the development of PI‐IBS.